On ways of improving national criminal procedure law in the fight against terrorism - Черниш, Роман Федорович (Problems of legality, 2016)
The article analyzes certain provisions of the criminal procedure law regarding preventive measures to the subjects, reasonably suspected of committing crimes against national security and public safety. The study concludes that the situation in which the person is reasonably suspected of having committed one of the worst category of crimes – against national security and public safety, it is difficult to apply the preventive measure is unacceptable. After investigators and prosecutors is problematic as part of the pre-trial investigation to collect, given the objective circumstances (commission of an offense in the temporarily occupied territories of Ukraine) a sufficient amount of material (evidence) that might argue the need to apply suspect this exclusive preventive measures as detention custody.In order to eliminate preconditions to avoid persons involved in the commission of crimes against national security, criminal liability due to excessive democratization of national criminal and criminal procedural law, we consider it appropriate to amend the Criminal Procedure Code of Ukraine, which provide for the applicability of the person suspected of committing illegal acts above categories, all precautions set forth in Code of Ukraine provided the objective reasons at the time of announcement of suspicion cannot collect enough hard evidence to substantiate in court to elect a preventive measure in the form of detention (investigator in agreement with the prosecutor will act on petition the court to apply to suspect another preventive measure provided for in art. 176 Criminal Procedure Code of Ukraine). Another area outlined solving problematic issues can serve to simplify the legislative mechanism of a preventive measure in the form of detention for this category of offenders.